Guillain-Barré syndrome outbreak in Tapachula temporally associated with the Zika virus introduction in Southern Mexico. (19th October 2022) - Rodríguez de la Rosa, Ricardo Paul; Cano-Torres, J. Oggún; Rosales, Sonia; Kleinert, Anke Paula; Gómez, Arturo; George, Fernando; George, José; Piedad García, Mariana; Nájera-Cancino, Gabriel; Guerra-de-Blas, Paola del Carmen; Belaunzarán-Zamudio, Pablo F; Beigel, John; et al.
Abstract: The Guillain-Barré syndrome (GBS) has been previously associated with Zika virus infection. We analysed the data from all the patients with GBS diagnosis that were admitted to a referral hospital, in Tapachula City during the period from January 2013 to August 2016, comparing the incidence of GBS according to the temporality of the Zika outbreak in Southern Mexico. Additionally, we described the clinical and epidemiological characteristics of the GBS patients admitted before or after the Zika outbreak. We observed a sharp increase in the number of patients hospitalised due to GBS from the time the first confirmed Zika cases appeared in Mexico. Clinically we observed GBS cases before zika outbreak had more frequently history of respiratory/gastrointestinal symptoms and GBS during zika outbreak had significantly more frequently recent history of rash/conjunctivitis. Although we cannot affirm that the increased cases of GBS have a specific aetiologic association with Zika, our results suggest that this observed outbreak of in Tapachula, might have been associated to the emerging Zika epidemic, locally and suggests that rare complications associated with acute infections (such as GBS) might be useful in the surveillance systems for emerging infections.